The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1177/001440290306900402
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators in Scaling up Research-Based Practices

Abstract: heightened focus in the field on trying to bridge this research-to-practice gap, many researchers have experienced more than a modicum of success in facilitating teachers' use of research-based methods (Abbott, . We now know more about how to conduct professional development programs that support teachers' sustained implementation of new practices than we did a decade ago. Rather than the "sit and get" standalone workshops more prevalent in the past, successful efforts have focused on providing long-411 ABSTRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 22 publications
(20 reference statements)
2
84
0
1
Order By: Relevance
“…When interventions are implemented in the classroom, there are several factors that may impact accurate and consistent treatment implementation, including (a) the complexity of the intervention, (b) time and resources required to implement the intervention, (c) the teacher's perceptions of intervention effectiveness, (d) the match between the intervention and the teacher's teaching style, (e) the teacher's understanding of the intervention plan, (f) the availability of feedback regarding implementation accuracy and intervention effectiveness, and (g) the teacher's motivation to intervene (Klingner, Ahwee, Pilonieta, & Menendez, 2003;Witt, Noell, LaFleur, & Mortenson, 1997). Because all of these factors are important, treatment acceptability, which encompasses many of the mentioned variables, is considered to be critical in influencing treatment integrity and intervention success.…”
mentioning
confidence: 99%
“…When interventions are implemented in the classroom, there are several factors that may impact accurate and consistent treatment implementation, including (a) the complexity of the intervention, (b) time and resources required to implement the intervention, (c) the teacher's perceptions of intervention effectiveness, (d) the match between the intervention and the teacher's teaching style, (e) the teacher's understanding of the intervention plan, (f) the availability of feedback regarding implementation accuracy and intervention effectiveness, and (g) the teacher's motivation to intervene (Klingner, Ahwee, Pilonieta, & Menendez, 2003;Witt, Noell, LaFleur, & Mortenson, 1997). Because all of these factors are important, treatment acceptability, which encompasses many of the mentioned variables, is considered to be critical in influencing treatment integrity and intervention success.…”
mentioning
confidence: 99%
“…Teacher educators have discussed barriers to innovative teaching practices, indicating that school norms and culture have a strong influence on the beliefs and practices of new teachers, due to fear of censure and worry for their jobs [34]. Administrators play an important role in setting a climate that either supports teacher development or one that encourages blind adherence to standardized practices, is not evidence-based, and does not further student learning [34,36].…”
Section: Theoretical Basis For the Researchmentioning
confidence: 99%
“…The effect of having the researchers present in the classroom may have also influenced teachers and students. However, the SW-PBS professional development had been provided by the same university training team and, therefore, all staff and students were accustomed to having researchers present in a variety of school environments, including classrooms, and in a variety of roles, including resource support (Klinger, Ahwee, Pilonieta, & Menendez, 2003). In the case of this particular study, the ongoing presence of researchers was viewed as an asset given that research has indicated that participants' behaviors are less likely to be altered by the presence of outside observers when their presence has become familiar (Fox, Gunter, Davis, & Brall, 2000;Kazdin, 1982).…”
Section: Limitationsmentioning
confidence: 99%